THE EFFECT OF WORKLOAD AND JOB STRESS ON EMPLOYEE PERFORMANCE AT PT DELLIFOOD SENTOSA CORPINDO, TANGERANG REGENCY - Fitriyadi, Enjah Pipit; Juanda, Angga; Supratikta, Hadi (Yayasan Education and Social Center, 2025)
This study aims to determine the effect of Workload and Job Stress on the performance of PT Dellifood Sentosa Corpindo employees. The research method used is quantitative. The population in this study was 355 employees of PT Dellifood Sentosa Corpindo. PT Dellifood Sentosa Corpindo with a sample of 75 respondents taken using the Slovin sampling technique. The data collection technique used a questionnaire. The data analysis method used simple and multiple linear regression tests, correlation coefficients, coefficients of determination, partial t-tests, and simultaneous f-tests. The results of this study indicate that: there is an effect of Workload on the performance of PT Dellifood Sentosa Corpindo employees. This can be proven from the simple linear regression equation Y = 15.095 + 0.672 X1. The correlation value is 0.776 (strong). The coefficient of determination is 60.3%. The calculated t value for Workload is 10,522 > t table of 1.993 with a significance of 0.000 < 0.05. There is an influence of Job Stress on the performance of PT Dellifood Sentosa Corpindo employees. This can be proven from the simple linear regression equation Y = 6.438 + 0.825 X2. The correlation value is 0.901 (very strong). The coefficient of determination is 81.2%. t count > t table or (17.780 > 1.993) with a significance of 0.000 < 0.05. Simultaneously, there is an influence of Workload and Job Stress on PT Dellifood Sentosa Corpindo. This is proven from the multiple linear regression equation Y = 5.708 + 0.203X1 + 0.664X2. The correlation value is 0.915 (very strong). The coefficient of determination is 83.7%. The calculated F value > F table or (184.756 > 3.12) with a significance level of 0.000 < 0.05.